Adoption reunion : reclaiming the lost object : a psychoanalytic and object relations approach to understanding the adoptee's experience of reunion with the birth mother - Scordilis, Morag (Department of Social Development, 2023)
This study explores the adoptee's desire for, and experience of reunion with the birth mother, from within a Psychoanalytic framework, and with an emphasis upon the Object Relations Theory perspective. Adoption reunion may be considered to be an attempt on the part of the adoptee to reclaim the lost object. There are numerous international studies on different aspects of adoption, however, South African studies are sparse. This study seeks to unite the dialectic of the clinical practitioner and adoption practitioner in order to provide a rich and meaningful understanding of post adoption practitioner in order to provide a rich and meaningful understanding of post adoption reunion in South Africa. The study is conducted from 'Within a non-probability framework and is an empirical ethnographic study with a predominantly qualitative, inductive approach, which is exploratory and descriptive in nature. The quantitative research provides width to the in-depth, qualitative data and takes the form of a content analysis. The qualitative aspect of the study employs an in-depth, face- to- face, unstructured interviewing technique, followed by an interview schedule. This approach enables the researcher to enter the world of the adoptee and render it understandable through providing an ''insider" view of the personal narratives and experiences of the subjects. The qualitative sample is comprised of 8 adult adoptees, who experienced face-to-face reunion with the birth mother, while the quantitative sample is comprised of 207 contacts named in the post adoption register of Cape Town Child Welfare between 1989 and i995. The conclusion drawn from the study is that the adoptee's desire for reunion is a health -promoting process which may be motivat0d by both external, social factors as well as intra-psychic forces; the latter resulting from the interruption of early psychic processes. Reunion is seen to be a response to these forces and enables adoptees to establish a mom coherent and integrated sense of Self, and to place themselves within an historical and biological narrative. Adoptees, whilst seeking to reclaim the lost object, do so as a means of reclaiming and completing the Self, the development of which was disturbed as a result of premature Interruption of the primary infant-mother bond. it is further concluded that the value of reunion is not synonymous with the success or outcome of reunion or of the adoption, that the majority of reunion comics are discontinued, and that a negative adoption experience is not more likely to result in the adoptee seeking reunion. Furthermore, reunion constitutes a form of retrospective mourning, which sets the adoptee free to relinquish ties to the lost object and to reclaim Self.